Implementation and Operational Research: Age Distribution and Determinants of Invasive Cervical Cancer in a "Screen-and-Treat" Program Integrated With HIV/AIDS Care in Zambia. (1st September 2015) - Kapambwe, Sharon; Sahasrabuddhe, Vikrant V.; Blevins, Meridith; Mwanahamuntu, Mulindi H.; Mudenda, Victor; Shepherd, Bryan E.; Chibwesha, Carla J.; Pfaendler, Krista S.; Hicks, Michael L.; Vermund, Sten H.; Stringer, Jeffrey S. A.; Parham, Groesbeck P.
Abstract : Background: Cervical cancer screening efforts linked to HIV/AIDS care programs are being expanded across sub-Saharan Africa. Evidence on the age distribution and determinants of invasive cervical cancer (ICC) cases detected in such programs is limited. Methods: We analyzed program operations data from the Cervical Cancer Prevention Program in Zambia, the largest public sector programs of its kind in sub-Saharan Africa. We examined age distribution patterns by HIV serostatus of histologically confirmed ICC cases and used multivariable logistic regression to evaluate independent risk factors for ICC among younger (⩽35 years) and older (>35 years) women. Results: Between January 2006 and April 2010, of 48, 626 women undergoing screening, 571 (1.2%) were diagnosed with ICC, including 262 (46%) HIV seropositive (median age: 35 years), 131 (23%) HIV seronegative (median age: 40 years), and 178 (31%) of unknown HIV serostatus (median age: 38 years). Among younger (⩽35 years) women, being HIV seropositive was associated with a 4-fold higher risk of ICC [adjusted odds ratio = 4.1 (95% confidence interval: 2.8, 5.9)] than being HIV seronegative. The risk of ICC increased with increasing age among HIV-seronegative women and women with unknown HIV serostatus, but among HIV-seropositive women, the risk peaked around age 35 and nonsignificantly declined with increasing ages. Other factors related to ICC included being married (vs. being unmarried/widowed) in both younger and older women, and with having 2+ (vs. ⩽1) lifetime sexual partners among younger women. Conclusions: HIV infection seems to have increased the risk of cervical cancer among younger women in Zambia, pointing to the urgent need for expanding targeted screening interventions. Abstract : Supplemental Digital Content is Available in the Text.